TAI CHI SEBAGAI MODALITAS REHABILITASI STROKE - Jimmy Jimmy; Yudy Goysal; Andi Kurnia Bintang; Muhammad Iqbal Basri; Nilla Mayasari (NEURONA, 2019)
TAI CHI AS A MODALITY FOR STROKE REHABILITATIONABSTRACTTai Chi is a Chinese traditional mind-body exercise and is well known for its slow and graceful movements. Tai Chi has been practiced for centuries and has become a popular exercise worldwide in recent years. Tai Chi is beneficial to cardiorespiratory function, muscular strength, balance, flexibility, microcirculation, psychological profile and quality of life. Tai Chi can be prescribed as an alternative exercise programme for selected patients with cardiovascular, orthopaedic, or neurological diseases. Recent studies prove that Tai Chi is safe and effective for patients with neurological diseases (e.g., stroke, Parkinson’s disease, traumatic brain injury, multiple sclerosis, cognitive dysfunction). Tai Chi appears to be beneficial for the rehabilitation of stroke, a leading cause of disability worldwide.Keywords: Rehabilitation, stroke, Tai ChiABSTRAKTai Chi adalah suatu latihan pikiran-badan tradisional Tiongkok dan terkenal dengan gerakannya yang lambat dan anggun. Tai Chi telah dipraktikkan selama berabad-abad dan telah menjadi latihan populer di seluruh dunia dalam beberapa tahun terakhir. Tai Chi bermanfaat untuk fungsi kardiorespirasi, kekuatan otot, keseimbangan, kelenturan, mikrosirkulasi, psikologis dan kualitas hidup. Tai Chi dapat diberikan sebagai program latihan alternatif untuk pasien dengan penyakit kardiovaskular, ortopedis, dan neurologis. Penelitian terkini membuktikan bahwa Tai Chi adalah aman dan efektif untuk pasien dengan penyakit-penyakit neurologis (seperti stroke, penyakit Parkinson, cedera otak traumatik, multipel sklerosis, disfungsi kognitif). Tai Chi tampaknya bermanfaat untuk rehabilitasi stroke, suatu penyebab utama kecacatan di seluruh dunia.Kata kunci: Rehabilitasi, stroke, Tai Chi